1999
DOI: 10.1023/a:1002432032354
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study was performed in order to evaluate the effect of vitrectomy in eyes with retinal vein occlusion associated with macular edema. Twenty-nine years eyes (27 patients) with branch retinal vein occlusion (BRVO), and 14 eyes (13 patients) with central retinal vein occlusion (CRVO) both associated with macular edema underwent phacoemulsification, intraocular lens implantation, pars plana vitrectomy and peeling of the posterior hyaloid membrane. Follow-up ranged from 12 to 32 months. Macular edema was reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(25 citation statements)
references
References 2 publications
1
24
0
Order By: Relevance
“…We performed PPV in CRVO patients with macular edema because it was recently reported that PPV is a useful surgical technique for the treatment of macular edema due to CRVO and improvement of visual acuity [13,14]. In contrast, the Central Vein Occlusion Study Group concluded that treatments targeting the secondary effects of venous occlusion, such as grid laser photocoagulation for macular edema and prophylactic panretinal laser photocoagulation for nonperfused CRVO, fail to improve visual acuity [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed PPV in CRVO patients with macular edema because it was recently reported that PPV is a useful surgical technique for the treatment of macular edema due to CRVO and improvement of visual acuity [13,14]. In contrast, the Central Vein Occlusion Study Group concluded that treatments targeting the secondary effects of venous occlusion, such as grid laser photocoagulation for macular edema and prophylactic panretinal laser photocoagulation for nonperfused CRVO, fail to improve visual acuity [16].…”
Section: Discussionmentioning
confidence: 99%
“…The institutional review boards of the Tokyo Women’s Medical University and Hiroshima University both approved the protocol for the collection and testing of vitreous fluid. PPV was performed because it has been reported that macular edema and visual acuity can be improved in CRVO patients by this procedure [13,14]. Consecutive patients presenting with CRVO between June 2003 and August 2007 were screened according to the following criteria and 27 patients were enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we were able to demonstrate that the posterior vitreous adhesion status may play a pivotal role in the development of CRVO [6]. Hence, the induction of a complete posterior vitreous detachment (PVD) offers a definite advantage for the involved patient as demonstrated in CRVO eyes undergoing pars plana vitrectomy [7]. Enzymatic vitreolysis as a novel approach can also be used to induce PVD development, and some major advantages have been attributed to the latter technique [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible that the key role in this surgery is played by the simple vitrectomy [82]. Pars plana vitrectomy with the creation of a posterior vitreous detachment was previously found to lead to a reduction in ME and a functional improvement in BRVO [83,84,85]. …”
Section: Treatmentmentioning
confidence: 99%